2017
DOI: 10.1186/s12898-017-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Complementing endozoochorous seed dispersal patterns by donkeys and goats in a semi-natural island ecosystem

Abstract: BackgroundEndozoochory is, in grazing systems, a substantial vector for seed dispersal. It can play an important role in vegetation dynamics, especially in colonization processes through seed input on the vegetation and on the soil seed bank. We investigated the endozoochorous seed input of donkeys and goats on a semi-natural island ecosystem in the Mediterranean. Through germination experiments, we assessed the viable seed content of the dung of these grazing animals to estimate their suitability and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…On the other hand, the higher within-population variability observed could be explained by migration of individuals across H. marinum populations, which could occur via seed dispersal by grazing animals and human activity. Treitler et al (2017) showed that donkeys and goats feed on and disperse species of the temporarily wet grassland, such as H. marinum, by endozoochory. In Tunisia, donkeys and goats have been moved widely around Tunisia since historic times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the higher within-population variability observed could be explained by migration of individuals across H. marinum populations, which could occur via seed dispersal by grazing animals and human activity. Treitler et al (2017) showed that donkeys and goats feed on and disperse species of the temporarily wet grassland, such as H. marinum, by endozoochory. In Tunisia, donkeys and goats have been moved widely around Tunisia since historic times.…”
Section: Discussionmentioning
confidence: 99%
“…Treitler et al . (2017) showed that donkeys and goats feed on and disperse species of the temporarily wet grassland, such as H. marinum , by endozoochory. In Tunisia, donkeys and goats have been moved widely around Tunisia since historic times.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2013), though one study mentioned up to 13 ungulates in South Africa (Milton and Dean, 2001). Second, most of the studies involved wild ungulates; and domestic ungulates were mentioned more rarely (Mitlacher et al, 2002;Cosyns et al, 2005;Mouissie et al, 2005b;Benthien et al, 2016;and Treitler et al, 2017, Table 3).…”
Section: Overlap and Complementarity Of Ungulate-mediated Dispersalmentioning
confidence: 99%
“…PlL represents one of the most typical shrubs in the Mediterranean maquis (shrubland) of Europe, Morocco, Turkey, Iraq and Iran [ 17 ]. In Italy, it is characteristic of the sensitive ecosystem, like that of Sardinia [ 18 ], where it grows along the coast up to 700 m above sea level.…”
Section: Botany and Taxonomymentioning
confidence: 99%
“…One of the oldest dates back to the Nuragic civilization (1800 to 238 BCE) and was ascribed to the Sardinian population: the oil obtained by cold-pressing the berries was widely used for social purposes, i.e., home or votive lighting lamps, cooking, as well as as a popular remedy [ 17 ]. This habit is attested to by the presence of residues of “olium lentiscinum” often found during archaeological excavations in “torcularia” (ancient oil mills) [ 18 ].…”
Section: Historical and Cultural Usementioning
confidence: 99%